Cabaran bahagian jabatan siasatan narkotik IPD Pasir Puteh dalam membenteras jenayah rentas sempadan di perairan Malaysia (Pasir Puteh) (2013-2017) - Halmi, Ghani (2019)
Malaysia’s geographical location which is close to the Golden Triangle, the main drug producer in Southeast Asia, makes it vulnerable to drug smuggling. Kelantan that borders Thailand becomes the target of drug trafficking which is not only done through land route but also through sea route. This study aims to identify the roles and the responsibilities as well as the challenges that the Narcotics Criminal Investigation Division of Pasir Puteh has to face in combating drug smuggling in their maritime areas. This study has three main objectives, namely to identify the involvement of the Narcotics Criminal Investigation Division of Pasir Puteh in addressing the issue of drug smuggling through the sea route; nesides to study the internal challenges and the external challenges faced by the Narcotics Criminal Investigation Division of Pasir Puteh in addressing the issue of drug smuggling through the sea route. This study is a qualitative study which mainly uses interviews in getting data. Five members of the Narcotics Criminal Investigation Division of Pasir Puteh and eight civilians, consisting of smuggler, distributor, buyer and resident, are selected as respondents to get information and achieve the goals of the study. This study finds that there are two factors that contribute to the problem in eradicating drug smuggling, which are internal factors and external factors. The internal factors that have been identified are problems in the spheres of human resources, logistics and staff integrity. The external factors that have been discovered, meanwhile, are overlapping jurisdictions with other agencies, lack of cooperation from the locals, limitation in existing act and power, smuggler’s tactics, and the geographical, economical, and social situation of Malaysia. Finally, this study provides recommendations which are deemed to be appropriate and relevant to the Narcotics Criminal Investigation Division of Pasir Puteh in particular, and to the Royal Malaysian Police in general, so that they can always move forward in combating cross-border crime through the sea route.